Light-emitting electrochemical cells based on conjugated ion gels - Kushida, Soh; Kebrich, Sebastian; Smarsly, Emanuel; Strunk, Karl-Philipp; Melzer, Christian; Bunz, Uwe H. F. (ACS applied materials & interfaces, 2020)
π-conjugated gels are potentially useful for organic electronic applications. We present a π-conjugated ion gel, composed of substituted poly(para-phenyleneethynylene) (PPE) and an ionic liquid. This combination is well suited as an active material in a light-emitting electrochemical cells (LECs). The nanosegregated structure of the gels achieves a large interface between the polymer and ionic liquid (IL) and allows—by nature of its structure—facile ion conduction and continuous electrical conduction paths. Efficient doping significantly improves the response time. This concept should be applicable to other π-conjugated gels, and it allows the construction of gel-LECs.
Gesehen am 02.10.2020